VENUE: Virtualized Environment for Multi-UAV Network Emulation - Victor Sanchez-Aguero; Francisco Valera; Borja Nogales; Luis F. Gonzalez; Ivan Vidal (IEEE Access, 2019)
Unmanned Aerial Vehicles (UAVs) have progressively been integrated into people lives during the last years. It is quite common now to see UAVs flying in the countryside doing field inspection, in highways for traffic control operations, or above stadiums in sport and music events. It is also common to see spectacular UAV swarm showcases (in most cases they are just performing a choreography) showing the potential of upcoming technologies. This article is focused on multi-UAV scenarios, on the establishment of Flying Ad hoc Networks (FANETs), and on the integration of 5G technologies like Network Function Virtualization (NFV) or Software Defined Networking (SDN). In particular, this article presents a proposal for one of the most common problems that the research and development community has to face at some stage: the validation of the different solutions and deployments. In this area, there is currently a notorious gap between the design phase and the deployment phase, since traditional network simulators are not designed with the constraints imposed by UAVs in mind. Besides, services implementations (that are usually distributed into single-board computers carried as payloads by UAVs) cannot be easily combined with the simulators. VENUE (Virtualized Environment for multi-UAV network emulation) is presented as an experimentation platform that allows testing the integration of multi-UAV FANETs together with network services deployments. VENUE covers from the simulation/emulation phase up to the real equipment integration phase. The validation of the platform is also presented in this article through several UAV use cases that make use of NFV technologies.